2021
DOI: 10.1002/pbc.29261
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic multicentric Castleman disease with TAFRO clinical subtype responsive to IL‐6/JAK inhibition: A pediatric case series

Abstract: TAFRO (thrombocytopenia, anasarca, fever/elevated C‐reactive protein, reticulin myelofibrosis, renal dysfunction, and organomegaly) clinical subtype of idiopathic multicentric Castleman disease (iMCD‐TAFRO) is a rare lymphoproliferative disease characterized by systemic inflammation. First‐line treatment for iMCD‐TAFRO includes steroids and interleukin (IL)‐6 blockade. Many patients have refractory disease, which is associated with significant morbidity and mortality, and treatment remains challenging. We pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In this article, Patient 5 was ultimately diagnosed with TAFRO syndrome. So far, there have only been ve reports of pediatric TAFRO syndrome overseas [12,[23][24][25][26] . In this article, Patient 5, who had concurrent TAFRO syndrome, initially presented with fever and edema in the limbs, progressive thrombocytopenia, and small amounts of effusion in multiple serous cavities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, Patient 5 was ultimately diagnosed with TAFRO syndrome. So far, there have only been ve reports of pediatric TAFRO syndrome overseas [12,[23][24][25][26] . In this article, Patient 5, who had concurrent TAFRO syndrome, initially presented with fever and edema in the limbs, progressive thrombocytopenia, and small amounts of effusion in multiple serous cavities.…”
Section: Discussionmentioning
confidence: 99%
“…The main treatment methods are IL-6 receptor monoclonal antibody (tocilizumab) and IL-6 antibody (siltuximab). For some children whose treatment with tocilizumab was not effective, previous studies have shown that combination chemotherapy can achieve certain effects, such as the CHOP regimen, LD (lenalidomide, dexamethasone) regimen, etc [11,12] . In addition, thalidomide, cyclosporine, oral corticosteroids, and sirolimus have also been reported to be used in the treatment of iMCD [11,13] .…”
Section: Treatment Planmentioning
confidence: 99%
“…Two reports of ruxolitinib use in pediatric and adult cases of iMCD-TAFRO syndrome have been reported. [19,20] Therefore, we report 2 rare cases of ruxolitinib use in adults with the iMCD-TAFRO syndrome. However, further prospective studies should confirm the efficacy of JAK inhibitors for the treatment-resistant and refractory iMCD-TAFRO syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…4 iMCD disproportionately affects adults, with a median age of diagnosis of 50 years, and there are very few published pediatric cases. 5,6 We report the case of an adolescent diagnosed with iMCD-TAFRO 6 weeks after hospitalization with an acute SARS-CoV-2 infection.…”
Section: Idiopathic Multicentric Castleman Disease In An Adolescent D...mentioning
confidence: 99%